PENGARUH PENERAPAN METODE TALKING STICK MELALUI MEDIA AUDIO TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN MATEMATIKA PADA SMPN 13 MATARAM TAHUN PELAJARAN 2018/2019 - Zulkhairah, Zulkhairah; Abidin, Zainal; Kurniawan, Ade; Sabrun, Sabrun (Jurnal Ilmiah IKIP Mataram, 2020)
This study aims to determine whether or not there is an effect of the application of the talking stick method through audio media on student learning outcomes in mathematics in SMP 13 Mataram in 2018/2019 school year. The type of research used is experimental (quasi-experimental), and the design used is nonequivalent control group design, as for the saturated sampling technique where the sample in this study in two classes, namely in the experimental class amounted to 30 people and the control class numbered 30 people. data retrieval of student learning outcomes obtained using the instrument in the form of description. the data obtained were analyzed using the t-test significance level of 5%, the results of calculations showed that the t-test value was 2.1614 >Â ttable11.070 so it can be concluded that there was an influence of the Talking Stick learning model on student learning outcomes at SMP 13 Mataram in the school year 2018/2019.